An accurate and simplified small signal parameter extraction method for GaN HEMT. (8th March 2019) - Khusro, Ahmad; Hashmi, Mohammad S.; Ansari, Abdul Quaiyum; Mishra, Aditya; Tarique, Mohammad
Summary: In this paper, development of a small signal model for 2 × 200 μm GaN HEMT based on the conventional 20‐element model is presented. The proposed model presents a direct parameter extraction algorithm, instead of the hybrid optimization approach, that provides simplification, accuracy, and less computational complexity. The extrinsic elements are extracted using a modified cold pinch‐off condition while discarding the unwanted forward biasing of the gate. The negative drain to source capacitance Cds is also observed in the ohmic region (for smaller VDS ). An excellent agreement found between the measured and modeled data for a wide range of frequencies and bias values shows the effectiveness of the proposed approach. The proposed modeling technique is validated with a good agreement between the achieved bias dependency of intrinsic parameter values and the respective theoretical parameter values. Abstract : A systematic, simple, and direct extraction procedure is proposed for the development of small signal model for GaN HEMT. A very good agreement has been found between the measured data and the proposed model for a broad range of frequencies. Moreover, the negative value of drain to source capacitance C ds is observed in the ohmic region for different biasing values.